2015
DOI: 10.3945/ajcn.114.083303
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of intestinal transplantation for adult patients with intestinal failure: a simulation study

Abstract: Our simulations show that ITx slightly improves survival of patients with IF in comparison with HPN at an additional cost of €19,529 per life-year gained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 25 publications
0
16
0
5
Order By: Relevance
“…An economic evaluation study of pediatric small bowel transplantation in the United Kingdom showed mean costs up to 30 months of £207,000 for those transplanted or on the waiting list, and £159,000 for those stable on home PN [8]. A recent adult study showed that Home PN costs were V13,276 for treatment introduction, followed by V77,652 annually [9]. Home PN is thus very expensive.…”
Section: Cost Savingsmentioning
confidence: 99%
“…An economic evaluation study of pediatric small bowel transplantation in the United Kingdom showed mean costs up to 30 months of £207,000 for those transplanted or on the waiting list, and £159,000 for those stable on home PN [8]. A recent adult study showed that Home PN costs were V13,276 for treatment introduction, followed by V77,652 annually [9]. Home PN is thus very expensive.…”
Section: Cost Savingsmentioning
confidence: 99%
“…Entsprechend der DGEM-S3-Leitlinie ist eine regelmäßige Laborkontrolle bestimmter Parameter notwendig, um neben der Prävention von Komplikationen eine bedarfsgerechte Anpassung der [7,24]. Eine 2015 in den Niederlanden erstellte ereignisorientierte Simulation über die Kosteneffizienz zwischen Dünndarmtransplantation und HPN zeigte einen geringfügigen Überlebensvorteil mit inkrementellem Kosten-Effektivitäts-Verhältnis von 19 529 € je zusätzlich überlebtes Jahr [25]. Aus Sicht der Autoren sollte eine entsprechende Evaluation bei chronischem Darmversagen (ESPEN IF Type III, [3]) frühzeitig erfolgen und gleichzeitig eine intestinale Rehabilitation an einem erfahrenen Zentrum durchgeführt werden.…”
Section: Kostenberechnung Der Ambulanten Labormedizinischen Leistungunclassified
“…Dentro del ámbito europeo de Reino Unido, Francia y Holanda, los estudios sugieren que, comparada con la alternativa de trasplante intestinal, la NPD resultó en un menor coste por año de vida al tiempo que parece ser claramente coste-efectiva comparada con el mismo tipo de tratamiento administrado en el hospital (42)(43)(44).…”
Section: ¿Es Coste-efectiva La Npd?unclassified